Legal Remedies for Resolving Land Disputes under Indonesia’s Positive Law : An Evaluation of Effectiveness and Justice - Moa, Fransiskus Rifandy; Djajaputra, Gunawan (PPPM, Sekolah Tinggi Ilmu Hukum (STIH) Biak-Papua, 2025)
Land disputes in Indonesia represent a complex structural issue, shaped by overlapping legal frameworks, weak administrative systems, and the limited recognition of indigenous peoples’ rights. This study aims to analyze the mechanisms for resolving land disputes based on positive law, identify key obstacles to their implementation, and evaluate their effectiveness in ensuring both legal certainty and substantive justice. Employing a normative legal approach and qualitative-descriptive analysis, the study draws on legal texts, court decisions, and relevant academic literature. The findings indicate that although positive law offers a formal framework for dispute resolution, its practical effectiveness is constrained by bureaucratic inefficiencies, unequal access to justice, and the marginalization of customary law. In contrast, alternative mechanisms—such as mediation and customary law-based processes—have demonstrated greater adaptability to local contexts and socio-cultural realities. The study concludes that an integrative approach, combining the normative structure of positive law with non-litigation mechanisms rooted in local values, is essential for developing an effective and equitable land dispute resolution system in Indonesia.